A Bulky Pyridinyl?uorene/Triphenylamine Hybrid Used as Host Material for Heavily‐Doped Blue Electrophosphorescent Devices. Issue 4 (3rd February 2016) - Zhao, Xianghua; Wu, Yukun; Zhou, Li; Wu, Nana; Tang, Lin; Zhao, Yi; Li, Xiaosheng; Ding, Dongxue; Xu, Hui
Abstract: In this work, a novel molecule pyridinyl?uorene/triphenylamine hybrid (TPyFTPA ) with bulky steric hindrance effects has been synthesized successfully by substituting 9‐(pyridine‐2‐yl)‐fluoren‐9‐yl with triphenylamine (TPA) via Friedel‐Crafts reaction, which possesses good thermal stability and triplet energy ( E T ) of 420°C with 5% weight loss and 2.86 eV, respectively. Moreover, the bulky steric hindrance material shows high stable morphology by heating to 200°C without finding melting phenomena and crystallization that is demonstrated by differential scanning calorimetry (DSC) curve. The bulky pyridinyl?uorene end‐capped TPA has been used as host material for blue phosphorescent organic light‐emitting diodes (PhOLEDs) with maximum external quantum efficiencies (EQEs) of 2.7%, 3.7%, and 3.5%, at the doping ratios of 10%, 30%, and 40%, respectively. The performances ofTPyFTPA ‐based blue PhOLEDs own wide concentration ranging from 10% to 40%, which indicates the bulkyTPyFTPA might be a potential candidate for inexpensive products with simplifying process for the applications in full‐color display and solid state lighting. Abstract : The performance ofTPyFTPA ‐based blue PhOLEDs show wide independent concentration ranging from 10% to 40%, which indicates the bulkyTPyFTPA might be a potential candidate for simplifying fabircation process and inexpensive devices.